DIE BOU VAN DIE STAATSARTILLERIEKASERNE, POTGIETERSTRAAT, PRETORIA: DIE UITBREIDING IN 1924 OM DIE HOOFKWARTIER VAN DIE UNIEVERDEDIGINGSMAG TE HUISVES - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
This article describes the coming into existence of the State Artillery Baracks, Potgieter Street, Pretoria and the expansion in 1924 in order to accomodate Defence Headquarters. The attention of the reader is invited to an article by the same author, which appeared in Militaria 2 volume 2, on Defence Headquarters.